The Difficulty of Reintegration: Examining the Child Soldier’s Post-War Life in Selected African Novels - Yeboah, Philomena Ama Okyeso; Otoo, Paul; Freitas, Philip Kwame; Abdul-Basit, Mohammed (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Many research works on the child soldier phenomenon seem to focus largely on the war-time experiences of the child soldier. Consequently, great attention is given to the life of the child soldier during the war. This paper, through qualitative content analysis and the trauma theory (Cathy Caruth’s concept of belatedness and Dominick LaCapra’s concept of acting-out) pays particular attention to the child soldier’s life after the war and his preparedness towards reintegration. The difficulty that accompanies this exercise is what makes obvious the loss of the child soldier. Even though he is far away from the war, he becomes a troubled and lost child who struggles futilely to erase his war-time memories. The paper finds that the child soldier’s loss is often manifested in the form of extreme violence, post-traumatic stress disorder, identity crisis and the lack of trust. Also, the paper subtly questions rehabilitation as an absolute curative measure for the child who was once a vicious perpetrator of violence and chaos. The paper finds that although rehabilitation provides a serene environment for the former child soldier and attempts to normalize his difficult and painful memories in his present world, it does not completely heal him of his psychological pain and wound.